Diatomite enhanced dynamic membrane technology for simultaneous backwash sludge pre-dewatering and backwash wastewater recycling. (20th February 2019) - Li, Lucheng; Xu, Guoren; Xing, Jia
Abstract: A novel diatomite−enhanced dynamic membrane (DM) technology was investigated for simultaneous backwash sludge pre-dewatering and backwash wastewater recycling from the backwashing process of a biological aerated filter (BAF), which was much cleaner and more sustainable than coagulation or centrifugation process. In this study, the backwash wastewater was mixed with diatomite to enhance the formation of the DM layer, which played a key role in backwash wastewater filtration and sludge pre-dewatering. The entire DM filtration process was operated under gravity−driven mode (200 mm water head). The effluent turbidity was reduced to less than 6 NTU at a diatomite addition concentration of 0.6 g/L and was acceptable for reuse in the backwashing process. The backwash sludge was retained on the DM and pre-dewatered to a water content of 87% with 0.6 g/L diatomite addition; this greatly reduced the sludge volume, saving energy and chemicals in subsequent sludge disposal processes. The sludge water content in sedimentation with PACl/PAM was only reduced to 99.5% and the further centrifugation could achieve sludge water content of 97%. In summary, DM technology shows great potential for backwash sludge pre-dewatering and backwash wastewater reuse, simplifying the sludge dewatering process in BAFs. Graphical abstract: Highlights: High filtration flux is achieved in the diatomite enhanced DM filtration. DM filtration is more effective and energy-efficient in sludge pre-dewatering. Diatomite performs better than PACl and PAM in assisting sludge pre-dewatering. The filtered effluent in DM filtration can be recycled in the backwashing process.